Peculiarities of determining the circle of recipients of one-time financial assistance in case of death of a serviceman, person liable for military service or reservist under martial law (Law and Safety, 2023)
It has been proved that today the legislator has created a clear mechanism for the procedure for payment of a one-time financial assistance in the event of death of a serviceman, person liable for military service or a reservist (including a police officer), which indicates that they understand the importance of taking measures to ensure national security and defence in the context of a full-scale invasion of Ukraine by russian federation. It has been stressed that the issue of determining the list of persons who should be considered family members entitled to this social payment remains controversial.A scientific analysis of the content of the Law of Ukraine “On Amendments to the Law of Ukraine “On Social and Legal Protection of Servicemen and Members of Their Families” regarding the Appointment and Payment of a One-time Financial Allowance” dated 29 July 2022 No. 2489-IX has been carried out. It has been considered the Draft Law on the Institute of Registered Partnerships No. 9103 dated 13 March 2023, aimed at establishing a new concept of “registered partners” in family law, and the current Resolution of the Cabinet of Ministers of Ukraine “On Amendments to Clause 2 of the Resolution of the Cabinet of Ministers of Ukraine dated 28 February 2022 No. 168” dated 27 September 2022, No. 1066, which introduced new grounds for non-payment of a one-time financial assistance for the deceased, in terms of their compliance with the current legislation, relevance and validity of their adoption in the current conditions. The author's proposals for amendments to the Criminal Code of Ukraine related to high treason, collaboration, and aiding and abetting the aggressor state have been presented.The attention has been drawn to the emergence of new social phenomena which require appropriate regulation by the State, in particular, this concerns the possible emergence of new grounds for family formation in the future. The legal framework that regulates the concepts of “family”, “family members” and defines a specific list of family members is quite extensive and needs to be improved both in terms of its very design and in terms of clarifying the legal definition of the concepts of “family” and “family member” in the law. The necessity of addressing this issue at the level of the Family Code of Ukraine by enshrining the relevant definitions in it has been emphasised.
Keywords: one-time financial assistance; martial law; family; family members; death of a serviceman; person liable for military service or a reservist.